Pemetaan Budaya Organisasi Pada Penggabungan Perguruan Tinggi di Bawah Satu Yayasan - Stefanus Khrismasgung Trikusumaadi; Noviana Dewi (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The merging of Higher Education Organization has become the direction of guidance from the Ministry of Education and Culture in the context of improving the quality of higher education. In merging organizations, cultural differences are key elements that affect the effectiveness of the integration process. This research aims to map organizational culture in a private higher education which is the result of the merger of 2 academies . by a survey method. Data were taken using random stratification technique on 3 groups of employees from different organizations of origin. Organizational culture was measured using 24 questions Organization Culture Assessment Instrument (OCAI). The Kruskal Wallis test found that there were differences in the types of organizational culture in the three groups, the perceived organizational culture type was significantly different between the four types), and the expected type of organizational culture was different for the Clan, adhocracy, and Hierarchy types (p: 0, < 0.005) . Thus, this research show that the organizational culture of each group is stll relatively strong, and still shows difference in the type of culture expected in each group.